Inovasi Biopolybag Ramah Lingkungan dari Tandan Kosong Kelapa Sawit Diperkuat dengan Bahan Isian Sekam Padi - Saragih, Alviyer; Oktaviani, Oktaviani; Dwi Oktoria, Widi; Ekawati, Rina; Hetalesi Saputri, Lestari (Jurnal Agro Industri Perkebunan, 2022)
Used plastic in the form of polybags in the rehabilitation of plantation and agricultural land takes a very long time to be degraded naturally by sunlight (photodegradation) and soil microorganisms (biodegradation). One way to overcome this deficiency is to make bio polybags that function as nursery containers. This research aims to make biopolybags from empty fruit bunches (EFB) more environmentally friendly because they are easily decomposed into natural fertilizers for plants. The research was carried out from June to September 2021 at The Processing Technology Laboratory and Material Laboratory, LPP Polytechnic. Bio polybag is made in several stages, i.e. grinding, mixing of materials and adhesives, shaping, drying and mechanical testings. Mechanical tests carried out are compressive tests, tensile strength tests, and hardness tests, and to confirm the results, a density test was performed. Each mechanical property test was repeated three times. The samples represent each variation of the variables. The best bio polybag result is the bio polybag of EFB, which is reinforced by a 6 g rice husk filler with a tapioca adhesive of a measure of 20%. The highest test value obtained is: 1,495 kg.cm-2 for press strength value; 404,46 kgf.cm-2 (39,67 MPa) for tensile strength; and 63,99 HV for hardness value. The existence of this bio polybag is expected to replace the plastic that is difficult to degrade because it can decompose quickly, is more practical to be planted directly, and does not cause root damage during seedling.